Pemanfaatan portal basis data daring dalam validasi nama ilmiah jenis dan suku tumbuhan - Damayanto, I Putu Gede P.; Fastanti, Fandri S.; Dalimunthe, Syadwina H. (Berkala Ilmu Perpustakaan dan Informasi, 2020)
Introduction. The study of the validation of scientific name validation at the species and family level is not widely known. This study aimed to provide information about the process of scientific name validation at the species and family level. Data Collection Method. Data were collected from online portal databases regarding the scientific name of plant species and family. Data was analyzed in a descriptive-narrative manner. Results and Discussions. Validation of the scientific name of species and family of plants can be conducted by searching the latest publications and using the online database portals i.e. IPNI, POWO, Tropicos, The Plant List, and GBIF. IPNI and The Plant List provide more information about species names compared to others. POWO and GBIF provide the status of the plant names and complemented with photographs of the plants, specimens, and distribution maps. Tropicos provides names of families according to the latest APG IV classification. Conclusions. Validation through the online portal database is the fastest way, however, validation through the publication of the latest plant taxonomy revision publications is the most recommended. Validation can be initiated by using the online database portals and then confirmed by tracking the latest revised plant taxonomy publications.